2011
DOI: 10.1007/s00425-011-1348-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of two β-amylase genes (Bmy1 and Bmy2) in developing and mature barley grain

Abstract: Two barley (Hordeum vulgare L.) β-amylase genes (Bmy1 and Bmy2) were studied during the late maturation phase of grain development in four genotypes. The Bmy1 and Bmy2 DNA and amino acid sequences are extremely similar. The largest sequence differences are in the introns, seventh exon, and 3' UTR. Accumulation of Bmy2 mRNA was examined in developing grain at 17, 19, and 21 days after anthesis (DAA). One genotype, PI 296897, had significantly higher Bmy2 RNA transcript accumulation than the other three genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Both assays are fully consistent to each other and the protein assay validates transcription assay results. A high expression of β-amy1 17, 19 and 21st day after anthesis was very recently reported by Vinje et al [54]. They investigated four cultivars differing in the degree of expression; however, they included genotypes with different alleles and genetic backgrounds [55], whereas for assay validation, we selected three spring malting barley cultivars with similar pedigree and identical allele [23].…”
Section: Resultsmentioning
confidence: 83%
“…Both assays are fully consistent to each other and the protein assay validates transcription assay results. A high expression of β-amy1 17, 19 and 21st day after anthesis was very recently reported by Vinje et al [54]. They investigated four cultivars differing in the degree of expression; however, they included genotypes with different alleles and genetic backgrounds [55], whereas for assay validation, we selected three spring malting barley cultivars with similar pedigree and identical allele [23].…”
Section: Resultsmentioning
confidence: 83%
“…Previously, genome-wide gene expression studies have identified candidate genes affecting malting. Expression studies using qPCR (Potokina et al 2006;Vinje et al 2011), Microarray (Close et al 2004Potokina et al 2004;Watson and Henry 2005) and LongSAGE (White et al 2008) have shown the likely role of many malting genes such as α and β amylase, Cxp1. at different stages of seed germination.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it is necessary to understand the mechanisms involved in banana fruit development. The BAM family has been reported to participate in the plant development of many species such as apple [39] , Arabidopsis [17] , barley [18] , and rye [40] . In apple, the amount of BAM protein was markedly greater during fruit development [39] .…”
Section: Identification and Evolutionary Analysis Of Banana Mabam Genesmentioning
confidence: 99%
“…Two BAM genes in Arabidopsis regulate shoot development [17] . The expression of a distinct transcript, from the barley Bmy1 gene, suggested its potential involvement in grain development [18] . In rye, expression of two BAM genes changed significantly during seed development [40] .…”
Section: Identification and Evolutionary Analysis Of Banana Mabam Genesmentioning
confidence: 99%
See 1 more Smart Citation